2014
DOI: 10.1890/13-2317.1
|View full text |Cite
|
Sign up to set email alerts
|

Higher plant diversity promotes higher diversity of fungal pathogens, while it decreases pathogen infection per plant

Abstract: Abstract. Fungal plant pathogens are common in natural communities where they affect plant physiology, plant survival, and biomass production. Conversely, pathogen transmission and infection may be regulated by plant community characteristics such as plant species diversity and functional composition that favor pathogen diversity through increases in host diversity while simultaneously reducing pathogen infection via increased variability in host density and spatial heterogeneity. Therefore, a comprehensive un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
185
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(221 citation statements)
references
References 77 publications
16
185
2
1
Order By: Relevance
“…Although we can only speculate on the underlying mechanism, previous studies have shown that while plant species richness reduced pathogen loads, it increased pathogen diversity (Hantsch et al., 2013; Rottstock et al., 2014). A higher pathogen diversity, with a higher probability of spillover of pathogen species from one tree species to another in mixtures with more tree species, could lead to a more diversified response (owing to a more diverse set of pathogens) and defense induction of plants (Spoel, Johnson, & Dong, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we can only speculate on the underlying mechanism, previous studies have shown that while plant species richness reduced pathogen loads, it increased pathogen diversity (Hantsch et al., 2013; Rottstock et al., 2014). A higher pathogen diversity, with a higher probability of spillover of pathogen species from one tree species to another in mixtures with more tree species, could lead to a more diversified response (owing to a more diverse set of pathogens) and defense induction of plants (Spoel, Johnson, & Dong, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from other forest ecosystems indicate that we can expect negative effects of tree species richness on pathogen damage (Hantsch, Braun, Scherer‐Lorenzen, & Bruelheide, 2013; Rottstock et al., 2014). In contrast, and opposing results from temperate forests (e.g., Guyot, Castagneyrol, Vialatte, Deconchat, & Jactel, 2016; Kambach et al., 2016), findings from natural forests in our study region revealed positive effects of tree species richness on herbivore damage (Schuldt et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pinpointing the actual 'enemies' (and their interactions with other 'bad' and 'good guys'), such as herbivores (e.g. insects and nematodes (Bagchi et al 2014;de Deyn et al 2003;Knops et al 1999)) and pathogens (viruses, bacteria, and fungi (Maron et al 2011;Moore and Borer 2012;Packer and Clay 2000;Petermann et al 2008;Rottstock et al 2014)), has proven difficult, especially belowground (Alexander 2010). There is interest in the role of fungal pathogens to explain the maintenance of biodiversity (Bever et al 2015;Gilbert 2002), but in this review we focus on the other way around: the role of plant species diversity to reduce the build-up of soilborne fungal disease (Latz et al 2012;Mommer et al 2018;Yang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…R 2 (regression coefficient) and P-values are shown next to significant fitted lines. Zhang et al 2010;Eisenhauer et al 2011;Rottstock et al 2014) may be due to root biomass production being mediated by other factors. Contrast to our question, facilitation among species did not lead to positive effects of plant diversity on the soil microbial functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, actual observations showed positive (Stephan et al 2000;Zak et al 2003;Eisenhauer et al 2011;Lange et al 2015), negative or no response (Johnson et al 2008) of soil microbial biomass, activity and diversity to increasing plant diversity (Zhang et al 2010;Rottstock et al 2014). Soil micro-organisms are mostly heterotrophic; thus, they decompose plant material for food or use plant exudates (LorangerMerciris et al 2006).…”
Section: Introductionmentioning
confidence: 99%